Nourishment and Health: An Engine for Rural Development Study on Chhota Jagulia Gram Panchayat of North 24 Parganas District, West Bengal, India (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Maternal health and nutrition are essential components for rural development; especially in developing areas. The purpose of this report is to focus on the Chhota Jagulia Gram Panchayat located in the North 24 Parganas District of West Bengal in order to evaluate the relationship existing between nutrition, access to healthcare, and socioeconomic status of women living in this area. The methodology included the use of primary data collected through household surveys and secondary data obtained from census and government sources. The results show that women have become more aware of antenatal care as well as institutional delivery and diagnostic services. However, there are still several significant challenges that remain, such as early marriage, low income, inadequate practices related to postnatal care, few women employed, and lack of access to government welfare programs. Other nutritional issues that impact a women’s maternal health status include being underweight and suffering from anaemia. The research concludes by stating that enhancing maternal health through the development of health care infrastructure, increasing awareness, and providing women with access to educational and economic opportunities will help generate sustainable rural development.